Peran Organisasi Kerjasama Islam (OKI) sebagai Alat Diplomasi dalam Penyelesaian Konflik Israel - Palestina - abadi, fany anggun (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum, 2023)
AbstractIn the current era of globalization, it has become a very influential factor in the diplomacy of international relations, one of which is when globalization is widespread as in this diplomacy. In international relations there is diplomacy which is not only useful for official agendas where there are countries that play an important role which are the sole actor, more than that currently diplomacy is equipped with the latest issues. For this reason, a bridge or organization such as the OIC (Organization of Islamic Cooperation) is needed. The formulation of the problem is in the form of the OIC as a diplomatic tool in resolving the Israeli-Palestinian conflict. The purpose of this article is to argue that the OIC has great potential to become an effective mediator in resolving the Israeli-Palestinian conflict through peaceful and responsible Islamic diplomacy. The theory of this research argues that the OIC has great potential to become an effective mediator in resolving the Israeli-Palestinian conflict. This research is a descriptive study with qualitative analysis techniques. In writing this article, namely analyzing the role of the OIC as a media between nations in the current era of globalization which promotes cooperation and peace to solve problems that are deemed appropriate to maintain and protect the vitality of Muslims.Keywords: OIC (Organization of Islamic Cooperation), Diplomacy, Globalization.